Penggunaan Model Altman Dalam Memprediksi Kondisi Keuangan Perusahaan di Masa Depan - Raflis, Ratnawati; Muthma'inah, Muthma'inah (Jurnal Ekonomi, 2013)
This research takes Altman Models for prediction the company financial condition in the future. Furthermore the models can predict the possibility of the company bankruptcy. The Manufactured Company that listed in BEI becames the samples of this research. And the result have the conclusion that some company that listed in 2004 has serious financial problem or having the possibilities for getting bankrupt. 33,3% from total samples are predicted to be insolvable. In 2005, there are 30% of the Company that having trouble in financial condition and the last in 2006. There are 26,7% Company that being predicted becones the bankrupt company. This information can be used by company to make correction in management. At the end we hope that the bankrupt prediction can noto be happenned in the future.